Hubungan Keputusasaan dengan Depresi Pada Pasien Diabetes Melitus Di Padang: The Relationship between Hopelessness and Depression in Diabetes Mellitus Patients in Padang - Rika Sarfika (NERS Jurnal Keperawatan, 2019)
Diabetes mellitus is a chronic disease that can cause depression in sufferers. Depression is often associated with feelings of despair. This study aimed to investigate the relationship between hopelessness and depression among patients diabetes mellitus.This research is analytical research with a cross-sectional study approach. 122 people with type 2 diabetes mellitus at Pauh and Andalas Public health center were designated as samples in this study with inclusion criteria not having a history of mood disorders or mental disorders (based on medical diagnosis), aged 25 - 65 years and willing to sign an informed consent form. Data collection was conducted from September to October 2016 using the SDS (Self-rating Depression Scale) questionnaire and BHS (Beck Hopelessness Scale) questionnaire. Data were analyzed using the Chi-Square Test.There is a significant relationship between hopelessness and depression among diabetes mellitus patients (Pv = 0.001). Patients with diabetes mellitus who experience despair have a risk of 7.03 times depression compared to patients who do not experience despair.Despair in patients with diabetes mellitus occurs due to negative thoughts about the disease in the future, lack of motivation in controlling blood sugar and negative expectations of the disease condition. These feelings make the patient depressed. Based on this, education needs to be given regarding diabetes mellitus and its treatment so that hopelessness can be anticipated.